Synthesis of tert-Butyl 1,3-Diaryl-3-oxopropylcarbamates by a Regiocontrolled Reduction of Ketoaziridines - Samimi, Heshmat A.; Yamin, Bohari M.; Saberi, Fatemeh (Synthesis, 2015)
A new, convenient approach for the reductive ring opening of N-H ketoaziridines is described. Treatment of N-H ketoaziridines with di-tert-butyl dicarbonate [(Boc)2O] in the presence of sodium iodide and nickel(II) chloride results in the corresponding tert-butyl 1,3-diaryl-3-oxopropylcarbamates by a regiocontrolled reaction. The structure of the regioisomeric product was confirmed by X-ray crystal structure analysis.
Keywords: aziridines; regioselectivity; ring opening; reduction; nickel(II) chloride